Autosomal dominant partial epilepsy with auditory features: A new locus on chromosome 19q13.11–q13.31. Issue 6 (1st March 2014) - Bisulli, Francesca; Naldi, Ilaria; Baldassari, Sara; Magini, Pamela; Licchetta, Laura; Castegnaro, Giovanni; Fabbri, Margherita; Stipa, Carlotta; Ferrari, Simona; Seri, Marco; Gonçalves Silva, Gilson Edmar; Tinuper, Paolo; et al.
Summary Objective To clinically and genetically characterize a large Brazilian family with autosomal dominant partial epilepsy with auditory features (ADPEAF) not related to leucine‐rich, glioma‐inactivated 1 (LGI1) gene. Methods Seventy family members (four married‐ins) participating in the study were assessed by a detailed clinical interview and a complete neurologic examination. Genetic mapping was conducted through autosome‐wide single nucleotide polymorphism (SNP) genotyping and subsequent linkage analysis on 16 and haplotype analysis on 25 subjects, respectively. Results The pedigree comprised 15 affected members, of whom 11 were included in the study (male/female: 6/5; mean age 39.5 years). All but two (III:22 and IV:92) had focal seizures with auditory aura followed by secondary generalization in 44.4%. The mean age at onset of epilepsy seizures was 13.7 years. Initial autosome‐wide SNP linkage analysis conducted on 12 subjects (8 affected) pointed to a single genomic region on chromosome 19 with a maximum multipoint logarithm of the odds (LOD) score of 2.60. Further refinement of this region through SNP and microsatellite genotyping on 16 subjects (11 affected) increased the LOD score to 3.41, thereby establishing 19q13.11–q13.31 as a novel ADPEAF locus. Haplotype analysis indicated that the underlying mutation is most likely located in a 9.74 Mb interval between markers D19S416 and D19S420. Sequence analysis of the most prominent candidate genes within this critical interval (SCN1B, LGI4, KCNK6, and LRFN1) did not reveal any mutation. Significance This study disclosed a novel ADPEAF locus on chromosome 19q13.11–q13.31, contributing to future identification of a second dominant gene for this epileptic syndrome. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.